Congenital papillomas and papillomatoses associated with the Human Papilloma Virus (HPV): report on 5 cases - Dias, Eliane Pedra; Barcelos, José Maria Pinto; Fonseca, Maria Evangelina Ferreira; Basso, Nédia Gomes da Silva (São Paulo Medical Journal, 1995)
The authors present a study of five cases of vulvar congenital papillomas and papillomatoses in stillborns and neonates dead upon birth. The studied material was collected from five necropsies. The histopathological evaluation showed hyperkeratosis, acanthosis, papillomatosis, perinuclear haloes, and nuclear abnormalities. In three of the cases, the electron microscopy identified nuclear and cytoplasmatic viral particles ranging from 40 to 60 nm in size, compatible with HPV. The immunohistochemical study of those lesions showed nuclear and cytoplasmatic positivity. The authors concluded that the presence of viral particles suggestive of HPV added to the immunopositivity indicated the possibility of viral infection.